Characterization of intra-litter variation on myogenic development and myogenic progenitor cell response to growth promoting stimuli - Vaughn, Mathew Alan (Kansas State University, 2017)
This series of studies focuses on the impact of intra-litter variation on fetal myogenesis, and the ability of porcine progenitor cells to respond to growth promoting stimuli. In study 1, the smallest (SM), median (ME), and largest (LG) male fetuses from each litter were selected for muscle morphometric analysis from gilts at d-60 ± 2 and 95 ± 2 of gestation. On d-60 and 95 of gestation LG fetuses had greater whole muscle cross-sectional area (CSA) than ME and SM fetuses, and ME fetuses had greater whole muscle CSA than SM fetuses. Indicating that SM and ME fetuses are on a delayed trajectory for myogenesis compared to LG fetuses. At d-60 the advanced trajectory of LG compared to ME fetuses was due to increased development of secondary muscle fibers; whereas, the advanced myogenic development of LG and ME fetuses compared to SM fetuses was due to the presence of fewer primary and secondary muscle fibers. At d-95 of gestation the advanced myogenic development of LG and ME was due to increased hypertrophy of secondary muscle fibers. For study 2, porcine fetal myoblasts (PFM) were isolated from SM, ME, and LG fetuses from d-60 ± 2 of gestation fetuses and for study 3, porcine satellite cells (PSC) were isolated from the piglet nearest the average body weight of the litter. Both myogenic cell types were utilized to evaluate effects of porcine plasma on proliferation, differentiation, and indications of protein synthesis. For the proliferation assay, cells were exposed to one of three treatments: high serum which consisted high-glucose Dulbecco's Modified Eagle Medium supplemented with 10% (vol/vol) fetal bovine serum, 2% (vol/vol) porcine serum, 100 U penicillan/mL, 100 µg of strepmycin/mL, and 20 µg of gentamicin/mL (HS), low serum which consisted of HS without 10% FBS (LS), and LS supplemented with 10% (wt/vol) porcine plasma (PP). Treatments for the differentiation and protein synthesis assays consisted of either HS or LS media that either contained porcine plasma at 10% (wt/vol; PPP) or 0% (wt/vol; PPN). The HS-PFM had a greater proliferation rate compared to the LS and PP-PFM, and PP-PFM had a greater proliferation rate compared to LS-PFM. The LG fetuses’ PFM had a reduced proliferation rate compared to SM and ME fetuses’ PFM, which were similar. The PPP-PFM had a decreased myotube diameter compared to PPN-PFM. Small fetuses’ PFM had a greater myotube diameter compared to ME and LG fetuses’ PFM, and ME fetuses’ PFM had a greater myotube diameter compared to LG fetuses’ PFM. The proliferation rate of PP-PSC was decreased compared to the HS- and LS-PSC, and HS-PSC had a greater proliferation rate compared to LS-PSC. The PPP-PSC had greater differentiation capacity and myotube diameter than PPN-PSC. In conjunction these results indicate divergent myogenic development among different fetal sizes within a litter and suggest that porcine plasma supplementation stimulates myogenic progenitor cell activity in an age specific manner.
Keywords: fetal myoblast; fetus size; muscle progenitor; myogenesis; porcine; porcine plasma